2011
DOI: 10.1103/physrevlett.107.027802
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Nematic Phase in Model Bent-Core Systems

Abstract: We study a class of models for bent-core molecules using low density version of Local Density Functional Theory. Arms of the molecules are modeled using two-and three Gay-Berne (GB) interacting units of uniaxial and biaxial symmetry. Dipole-dipole interactions are taken into account by placing a dipole moment along the C 2 symmetry axis of the molecule. The main aim of the study is to identify molecular factors that can help stabilizing the biaxial nematic phase.The phase diagrams involving isotropic (I), unia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…In the latter work, which assumes the same second-rank quadrupolar interaction, the dipolar interaction is more comprehensive and also depends on the relative position of the two interacting molecules. No polar phases were found in either study, in agreement with a density functional theory developed by Grzybowski and Longa, [26] a series of atomistic simulations by Peláez and Wilson [27] and a two-particle cluster theory by Osipov and Pajak. [28] However, by contrast, Ghoshal et al [25] suggested that the unrealistic Heisenberg form of dipolar interaction potential used by Bates [24] might form polar phases.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the latter work, which assumes the same second-rank quadrupolar interaction, the dipolar interaction is more comprehensive and also depends on the relative position of the two interacting molecules. No polar phases were found in either study, in agreement with a density functional theory developed by Grzybowski and Longa, [26] a series of atomistic simulations by Peláez and Wilson [27] and a two-particle cluster theory by Osipov and Pajak. [28] However, by contrast, Ghoshal et al [25] suggested that the unrealistic Heisenberg form of dipolar interaction potential used by Bates [24] might form polar phases.…”
Section: Introductionsupporting
confidence: 79%
“…We discuss the applicability of such a model later, but note here that other authors have used more realistic models for the dipolar interaction both in density functional theory, [26] lattice Monte Carlo simulations [25] and two-site cluster theory. [28] These studies include the effect of short-range order which, of necessity, do not appear in our molecular field theory.…”
Section: Discussionmentioning
confidence: 98%
“…33 A plethora of models have thus been devised to understand the three-dimensional bulk behavior of these systems. [40][41][42][43][44] Yet relatively little theoretical attention has been paid to related models in two dimensions. [45][46][47] Here, we consider the two-dimensional phase behavior of a bent-needle model in both its chiral zig-zag and achiral bow-shaped configurations (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical exploration of stable biaxial nematic order has been based on biaxial hard-body and Gay-Berne-type soft potential models, using specific particle shapes such as spheroplatelets [4,5], biaxial ellipsoids [6,7] and bent-core particles [8][9][10][11]. The biaxial nematic phase has also been found in binary mixtures of uniaxial plate-like and rod-like particles [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%